The Impact of Energy Production on the Introduction of ICT and the Growth of AIC in Kazakhstan - Sholpan Smagulova; Aigerim Yermukhanbetova; Kuralay Nurgaliyeva; Baimykhanova Sariya; Zhanymgul Baimukasheva; Almagul Manap; Gaini Koyshinova; Chulpan Akimbekova (International Journal of Energy Economics and Policy, 2023)
The presented work is devoted to the organization of the electric power industry and the agro-industrial complex of Kazakhstan. Here is given an economic analysis of the production capacity of the development of power plants. It is noted that more than 80% of electricity generation is carried out by coal-fired thermal power plants. Important attention is paid to the significant wear and tear of machinery and equipment at thermal power plants and state district power plants. The key focus of the work is on econometric modeling to identify patterns and quantify the impact of electricity production and digital farms on increasing agricultural production. The results of the regression model are substantiated using the applied statistical package EViews. A medium-term econometric forecast for the development of the agricultural sector is presented, considering the introduction of digital farms. Problems are revealed and measures to stimulate the construction of new energy facilities are considered. Also, proposals were made to enhance the use of investment projects of alternative energy sources in the country. At the same time, an important emphasis is considered at the level of enhanced development of ICT in the energy and agro-industrial complex. It has been established that the digitalization of the energy and agro-industrial complex sectors contributes to the economic growth of Kazakhstan.